Predictive Factors of Time Die From COVID-19 in Intensive Care Units - Gustavo Bergonzoli; Felipe Jose Tinoco Zapata; Carolina Jaramillo; Christian Jhoan Rodriguez C. (Universitas Airlangga, 2024)
To identify risk factors that increase or decrease the probability of dying from Covid-19 in Intensive Care Units (ICU) patients. This study is based on data collected retrospectively from the hospital records. The proportional model assumption was verified using the Kaplan–Meier method, and Cox Hazard Proportional Regression model to identify predictors' factors associated with time to death by Covid-19. Four factors were identified, two of them increase the probability of dying: age (Adjusted Hazard Ratio (HRa) = 1.032 (1.022–1.041), and breathing frequency HRa = 1.035 (1.016-1.054), and two decrease the probability: lymphocytes HRa = -0 815 (0.674–0.985), and diastolic pressure HRa = -0.992 (0.986–0.998). Every five years of increase in age the probability of dying does the same by 13.5%; while with an increase of three breaths there is an increase in the probability of dying equal to 7.4%. At the same time, five ml increase in mercury pressure will decrease mortality probability by 1.6%, while a 1.5 increase in lymphocytes will decrease it by 7.9%. Knowing these factors will undoubtedly be a useful tool to identify those patients who, due to their clinical condition, have a morbidity profile that classifies them as very high risk of dying, and therefore deserve personalized medical care.